Recombinant RoTat 1.2 variable surface glycoprotein as antigen for diagnosis of Trypanosoma evansi in dromedary camels - Lejon, Veerle; Claes, F.; Verloo, D.; Maina, M.; Urakawa, T.; Majiwa, Phelix A.O.; Büscher, Philippe (Elsevier, 2005)
The transcript encoding a predominant Trypanosoma evansi variable surface glycoprotein RoTat 1.2 was cloned and expressed as a recombinant protein in Spodoptera frugiperda and Trichoplusia ni (insect) cells. Its potential as an antigen for specific detection of antibody in serum of dromedary camels affected by surra, was evaluated. In ELISA, the reactivity of the recombinant RoTat 1.2 VSG was similar to that of native RoTat 1.2 VSG. An indirect agglutination reagent was therefore prepared by coupling the recombinant RoTat 1.2 VSG onto latex particles. The performance of the latex agglutination test was evaluated on camel sera, and compared with the performance of CATT/T. evansi and LATEX/T. evansi tests, using the immune trypanolysis assay with T. evansi RoTat 1.2 as a reference test. The relative sensitivity and specificity of the latex coated with recombinant RoTat 1.2 VSG, using a 1:4 serum dilution, were respectively, 89.3 and 99.1%. No differences were observed between the performance of latex coated with recombinant RoTat 1.2 VSG and LATEX/T. evansi or CATT/T. evansi. Here, we describe the successful use of the recombinant RoTat 1.2 VSG for detection of specific antibodies induced by T. evansi infections.